Competitiveness of hybrid and inbred rice with junglerice (Echinochloa colona) resistant to auxinic herbicides - Velasquez, Juan C.; Rodriguez, Diego; Alvarez, Maria Fernanda; Graterol, Eduardo; Sanabria, Yamid; Plaza, Guido; Roma-Burgos, Nilda (Frontiers in Agronomy, 2026)
Rice (Oryza sativa L.) is a crucial staple food crop, with significant production in Latin America, the Caribbean, and Asia. Weed infestations, such as with auxinic herbicide-resistant junglerice (Echinochloa colona), pose major challenges to rice production, underscoring the need for additional weed management tools, such as planting weed-competitive rice. This study evaluated the competitive ability of auxinic herbicide-resistant junglerice, with hybrid and inbred rice. Various junglerice accessions were collected and evaluated for their response to quinclorac at rates of 560 and 1,120 g a.i. ha−1. Subsequently, cross-resistance to florpyrauxifen-benzyl (FPB) was assessed using one accession with high resistance to quinclorac in dose–response assays. The intraspecific competitiveness of susceptible and resistant junglerice was evaluated in a replacement series experiment. Likewise, interspecific competitiveness of susceptible and resistant junglerice against inbred and hybrid rice was evaluated using the same approach. Large-scale testing with quinclorac indicated poor control of all junglerice accessions, achieving less than 70% control at the high rate. The one resistant accession (AR) tested showed 30-fold resistance to quinclorac and 2-fold resistance to FPB compared to the susceptible accession (UM). Under intraspecific competition, the resistant and susceptible junglerice were equally competitive, with a potential fitness penalty in the resistant population. The interspecific study suggested that, regardless of the resistance trait, junglerice was more competitive than the rice cultivars evaluated. AR biomass and leaf area exceeded those of inbred rice by ~115% and ~82% but exceeded hybrid rice by only ~70% and ~35%, respectively. This showed 21% and 26% lower relative advantage of inbred compared to hybrid rice. Breeding and planting competitive rice varieties is an ecologically viable strategy to combat weed resistance, especially in disadvantaged regions where other weed control options are limited.